True rheological behaviours of spacer fluid with consideration of wall slip effect. (4th February 2020) - Cao, Cheng; Pu, Xiaolin; Wang, Gui; Zhao, Zhengguo
Based on the modified coaxial cylindrical measuring systems, experiments on the rheological behaviours of spacer fluid have been done. Tikhonov regularisation is used to acquire the rheological parameters for its advantage. Then the characteristics of rheology and the wall slip effect of spacer fluid have been analysed in detail. The results show that wall slip effect tends to occur in the flow of spacer fluid and should be removed in the measurement of rheological behaviours. The apparent rheological behaviours can be characterised by Herschel-Bulkley model. However, it is far away from the true rheological behaviours of the spacer fluid, which can be characterised by Bingham model. The slip velocity of spacer fluid increases with the increases of wall shear stress. Besides, the critical wall shear stress of spacer fluid varies from 3.26 Pa to 16.64 Pa, and the wall slip effect of spacer fluid will occur even if in a low shear stress region. [Received: February 23, 2017; Accepted: January 9, 2018]